One-pot β-alkylation of secondary alcohols with primary alcohols catalyzed by ruthenacycles - Xu, Chang. (2013)
A ruthenacycle-catalyzed one-pot β-alkylation of secondary alcohols with primary alcohols is described. A survey of four C–N chelate ruthenacycles synthesized via the cyclometallation reaction of phenylmethanamine, N-methylphenylmethanamine, N,N-dimethylphenylmethanamine, and naphthalen-1-ylmethanamine with [(η6-C6H6)RuCl2]2 was undertaken. All four complexes were found to be active with the phenylmethanamine-based ruthenacycle showing the best combination of reactivity and product selectivity among the four. An expanded scope of substrates was also studied with the inclusion of unsaturated primary alcohols. The reactivity trend observed gave insights into the role of hydrogen bonding in the catalytic mechanism involving transfer hydrogenation between the substrates and the transition metal catalyst.